The knowledge and attitudes of midwives regarding legal and religious commandments on induced abortion and their relationship with some demographic characteristics - Narges Afhami; Parvin Bahadoran; Hamid Reza Taleghani; Nafisehsadat Nekuei (Wolters Kluwer Medknow Publications, 2016)
Background: Induced abortion is an important medical issue. Knowledge and attitude of midwives regarding legal and religious commandments on induced abortion can be useful in confronting this issue. The aim of this study was to assess the knowledge and attitudes of midwives of Isfahan regarding these rules and to find their relationship with demographic characteristics. Materials and Methods: This was a cross-sectional, descriptive, and analytical study. The study participants consisted of 189 midwives working in hospitals, health centers, private gynecology clinics, and university. Random quota sampling method was used. Data were collected using a researcher-made questionnaire. Data were analyzed using mean, frequency distribution tables, Pearson correlation, and Spearman's coefficient. For all tests, an error of less than 0.05 was considered. Results: The majority of the participants had extremely low to moderate (73%) knowledge about the subject of the study. Their attitudes toward effective implementation of these rules were mostly extremely weak to moderate (68.72%). No correlation was observed between knowledge, age, work experience, and education. However, there was a relationship between the level of knowledge about these rules and the location of service. There was no significant correlation between attitude and demographic characteristics. Conclusion: Due to less knowledge of the midwives and their low attitude score in this regard, training them, improving their attitude toward these issues, and effective implementation of these laws are necessary. Therefore, by identifying the factors affecting the formation of attitudes and the level of knowledge, more constructive proceedings can be taken to promote them.